Феномен ≪гендер-лидерства≫ в студенческой среде - Варава, А. И. (ХНУРЭ, 2012)
This work is devoted to the study of personality in the context of society as in large so in small groups. The modern development of psychology and sociology provides us with a rich soil for detailed study of the regulation of human behavior.